Effect of scaling back punishment on racial and ethnic disparities in criminal case outcomes. Issue 4 (4th June 2020) - MacDonald, John; Raphael, Steven
Abstract : Research Summary: In late 2014, California voters passed Proposition 47 that redefined a set of less serious felony drug and property offenses as misdemeanors. We examine how racial and ethnic disparities in criminal court dispositions in San Francisco change in the years before (2010–2014) and after (2015–2016) the passage of Proposition 47. We decompose disparities in court dispositions into components resulting from racial/ethnic differences in offense characteristics, involvement in the criminal justice system at the time of arrest, pretrial detention, criminal history, and the residual unexplained component. Before and after Proposition 47, case characteristics explain nearly all of the observable disparities in court dispositions between racial and ethnic groups. After the passage of Proposition 47, however, there is a narrowing of disparities in convictions and incarceration sentences that is driven by lesser weight placed on criminal history, active criminal justice status, and pretrial detention in effecting court dispositions Policy Implications: The findings from this study suggest that policy reforms that scale back the severity of punishment for criminal history and active criminal justice status for less serious felony offenses may help narrow inter‐racial and inter‐ethnic inequalities in criminal court dispositions. Efforts to reduce racial and ethnic inequalities in mass incarceration in other states should consider reforms that reduce the weight that criminal history, pretrial detention, and active probation status has on criminal defendants' eligibility for prison for less serious drug and property offenses.